Lives in the balance asylum adjudication by the Department of Homeland Security - Schoenholtz, Andrew Ian 1951-; Schrag, Philip G. 1943-; Ramji-Nogales, Jaya (New York Univ. Press, 2014)
"Although Americans generally think that the U.S. Department of Homeland Security is focused only on preventing terrorism, one office within that agency has a humanitarian mission. Its Asylum Office adjudicates applications from people fleeing persecution in their homelands. Lives in the Balance is a careful empirical analysis of how Homeland Security decided these asylum cases over a recent fourteen-year period. Day in and day out, asylum officers make decisions with life-or-death consequences: determining which applicants are telling the truth and are at risk of persecution in their home countries, and which are ineligible for refugee status in America.